Surfactant assisted disperser pretreatment on the liquefaction of Ulva reticulata and evaluation of biodegradability for energy efficient biofuel production through nonlinear regression modelling. (May 2018) - Kumar, M. Dinesh; Tamilarasan, K.; Kaliappan, S.; Banu, J. Rajesh; Rajkumar, M.; Kim, Sang Hyoun
Graphical abstract: Highlights: Chemo mechanical pretreatment enhance disintegration synergistically. This efficient method induces liquefaction at minimum specific energy of 437.1 kJ/kg TS. The VFA concentration of 782 mg/L was obtained from this incentive process. Chemo mechanical disintegration obtained a higher hydrogen production of about 63 mL H2 /g COD. Abstract: The present study aimed to increase the disintegration potential of marine macroalgae, ( Ulva reticulata ) through chemo mechanical pretreatment (CMP) in an energy efficient manner. By combining surfactant with disperser, the specific energy input was considerably reduced from 437.1 kJ/kg TS to 264.9 kJ/kg TS to achieve 10.7% liquefaction. A disperser rpm (10, 000), pretreatment time (30 min) and tween 80 dosage (21.6 mg/L) were considered as an optimum for effective liquefaction of algal biomass. CMP was designated as an appropriate pretreatment resulting in a higher soluble organic release 1250 mg/L, respectively. Anaerobic fermentation results revealed that the volatile fatty acid (VFA) concentration was doubled (782 mg/L) in CMP when compared to mechanical pretreatment (MP) (345 mg/L). CMP pretreated algal biomass was considered as the suitable for biohydrogen production with highest H2 yield of about 63 mL H2 /g COD than (MP) (45 mL H2 /g COD) and control (10 mL H2 /g COD).